Phosphorus Fluxes in a Restored Carolina Bay Wetland Following Eight Years of Restoration - Moorberg, Colby J.; Vepraskas, Michael J.; White, Jeffrey G.; Richter, Daniel D. (My University, 2023)
Restoring wetlands on agricultural land can release soil phosphorus (P) to surface waters. Phosphorus is a limiting nutrient in many freshwater systems, thus restricting its release will improve surface water quality by preventing algal blooms. A P balance was used to examine how P was cycling in a Carolina Bay wetland eight years after restoration from prior-drained agricultural land. The change in soil P was evaluated between archived samples taken at restoration (2005), and eight years after restoration (2013). Measured P fluxes included atmospheric deposition, plant uptake, and loss to surface water outflow. The soil total P pool at the time of restoration was 810 kg P ha-1. No significant (α=0.05) decrease in the soil P pool was observed over the eight years. Atmospheric deposition contributed 1.0 kg P ha-1 yr-1, plants incorporated 3.3 P ha-1 yr-1 into woody biomass and 0.4 kg P ha-1 yr-1 as forest floor litter, and 0.2 kg P ha-1 yr-1 was lost to surface waters draining the wetland. Because the loss of P to surface waters was small, and because runoff water concentrations of P declined through this period of study to concentrations below those likely to cause eutrophication (< 0.1 mg L-1), we concluded that the wetland was not contributing to the degradation of surface water quality of nearby streams following restoration. Further, isolated wetlands such as that studied may be promising sites for future wetland mitigation projects due to limited impacts on surface water quality.